Gyrotropy in Achiral Materials: the Coupled Oscillator Model. (10th September 2014) - Oates, Thomas W. H.; Shaykhutdinov, Timur; Wagner, Tolga; Furchner, Andreas; Hinrichs, Karsten
<x xml:space="preserve">Abstract</x> A coupled oscillator model is developed to explain the observation of gyrotropy in achiral metamaterials. By the action of distinct excitation modes, which only combine under oblique incidence, the measurement of circular birefringence in a split‐ring resonator (SRR) array is explained. The symmetry of the SRR resembles the water molecule, and parallels between the systems are drawn. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>